Meeting the industrial demand of construction engineering graduate competence - Ahmad Rifqi Asrib; Anas Arfandi (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2017)
The aim of this study is to identify the distribution and relevance of graduate competencies in S1 PTSP Department FT UNM to those in the world of work. This research was conducted for a year. The location of this research was conducted in according with the distribution of graduates. Samples amount 28 respondents. The data collected used questionnaires, interviews and documentation. The result shows that the waiting period of graduate majoring in engineering education buildings PTSP FT UNM within the last 3 years (2013-2015) in getting a job was an average of 4.4 months. Then, the relevance of the work with their educational background according to their expertise was 85.72% while 14.28% are not suitable. Furthermore, the level of relevance of graduates' technical skills in the field of building engineering was at the level of relevant amount 44.48%, and in the field of education at the level of highly relevant amount 55.00% of the number of observed respondents. The level of employability skills were in the proficient category with the average value about 48.75% of all aspects.